Ketakutan Akan Ketertinggalan (Fear of Missing Out/FOMO) dan Perilaku Konsumen: Arah Selanjutnya? (Analisis Bibliometrik dan Tinjauan Literatur Sistematis) - Anna Destriana Firmialy Samsura; Popy Rufaidah (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
This study aims to investigate the phenomenon of Fear of Missing Out (FOMO) about consumer behavior across three major academic fields: Business, Management, Economics, and Finance (BMEF); Social Sciences and Humanities (SSH); and Psychology and Decision Sciences (PSD). A Systematic Literature Review (SLR) was conducted using bibliographic tools such as VOS Viewer, Publish or Perish, and Mendeley to analyse 220 scientific publications indexed in the Scopus database and published by reputable sources, including Emerald, Sage, Wiley, and Elsevier. The analysis results show a significant research gap between “Fear of Missing Out” and “Consumer Behavior” in the targeted fields. The analysis identifies ten thematic clusters, each revealing the conceptual and disciplinary links between FOMO and consumer-related phenomena. This study highlights the key contributors, emerging subthemes, and influential publications that shape current understanding of FOMO across business, social sciences, and psychology. By bridging this research gap, this study underscores the importance of FOMO as a psychological construct that influences consumer engagement and purchasing behaviour in digital environments. The findings also suggest practical implications for marketers seeking to optimize digital marketing strategies by leveraging FOMO-driven triggers. Furthermore, this study provides valuable directions for future research on decision-making processes, consumer behaviour dynamics, and the psychological impact of digital technologies, while emphasizing the need for interdisciplinary approaches to deepen theoretical development and address ethical considerations in digital marketing practices.